Effectiveness of Group Counseling Services with Cognitive Restructuring Techniques to Increase Student Self-Efficacy at MTs Islamiyah Balen - Uyunul Fauziyah; Yanuari Srianturi (Journal of Education and Counseling (JECO), 2024)
Self-efficacy is an individual's belief regarding his or her ability to carry out tasks or actions required to achieve certain results. Self-efficacy is important for managing students' behavior and beliefs needed to achieve their goals and learning outcomes. Self-efficacy has three aspects or dimensions (1) level dimension, (2) strength dimension, and (3) generalization dimension. This research was conducted on class VII students at MTs Islamiyah Balen to determine the effectiveness of group counseling using cognitive restructuring techniques to increase students' self-efficacy. This research uses a quantitative approach with a Pre-experimental design with a One-Group Pretest-Posttest Design. As for data collection using self-efficacy instruments, observations, and interviews, purposive sampling techniques were used to select 8 samples from 104 respondents who would be provided group counseling services. Data analysis in this study used the One-Sample Kolmogorov-Smirnov Test for normality and the paired sample T-test. Based on the results of the paired sample T-test, it is known that the significance value is 0.000 < 0.05, so Ho is rejected and Ha is accepted, which means there is a significant difference. Group counseling research using cognitive restructuring techniques has proven effective in increasing students' self-efficacy at MTs Islamiyah Balen.